Plato's Academy : Its Workings and its History - Kalligas, Paulos (Cambridge University Press, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Illustrations -- List of Contributors -- Preface -- 1 Introduction -- 2 In the Shadow of Athena Polias: The Divinities of the Academy,the Training of Politai and Death in Service to Athens -- 3 Observations on the Topography of Ancient Academia -- 4 The Gymnasium of the Academy and the School of Plato -- 5 The Academy in Athenian Politics and Society - Between Disintegration and Integration: The First Eighty Years(387/6-306/5) -- 6 Plato in the Academy: Some Cautious Reflections -- 7 Plato and the Mathematics of the Academy -- 8 Euclid of Alexandria: A Child of the Academy? -- 9 The Study of Natural Kinds in the Early Academy -- 10 Approaches to the Pythagorean Acusmata in the Early Academy -- 11 Polemo, grosser Schatten of the Old Academy -- 12 One Academy? The Transition from Polemo and Crates toArcesilaus -- 13 Carneades' Theological Arguments -- 14 The End of the Academy -- 15 The Academy Through Epicurean Eyes: Some Livesof Academic Philosophers in Philodemus' Syntaxis -- Appendix -- Bibliography -- Index.